Factors Related to Fall Prevention Behavior of Patients with Knee Osteoarthritis in Watsalud Community Bang Phli District, Samutprakarn Province: Factors Related to Fall Prevention Behaviors of Patients with Knee Osteoarthritis in Watsalud Community Bang Phli District, Samut – Prakarn Province - wihok, kronwikran; กสิผล ทวีศักดิ์; จำปาเทศ นพนัฐ (Journal of Health Sciences and Wellness, 2021)
The purpose of this descriptive research was to study the preventive behavior of osteoarthritis patients, and to analyze factors such as sex, age, body mass index, severity of osteoarthritis, fall history, balance ability, and the confidence in balancing which were related to the fall preventive behavior of Osteoarthritis patients in Wat Salut community, Bang Phli District, Samut Prakan Province. We have sampled 280 knee osteoarthritis patients. The tool consisted of 5 questionnaires. The content of these questionnaires were validated by 3 experts. Reliability of the questionnaires were examined using Cronbach’s alpha coefficient at 0.73,0.80,0.90,0.98,0.94 and 0.77. Data analysis by descriptive statistics such as frequency, median and quartiles 1-3. Comparison fall prevention behaviors by using Mann-Withney U, Kruskal-Wallis test, and correlation analysis between osteoarthritis severity, and fall preventive behaviors of osteoarthritis patients by using Spearman’s rho. Data were collected between March– May 2020. The results showed that fall preventive behaviors (94.29%) were at a high level. The comparison of fall prevention behavior was classified by gender, age group, and fall history, and we found that different genders had the mean of fall preventive behavior statistical significance (Z = - 2.39, p<.05). Males had more fall prevention behaviors than females. A comparison of fall preventive behavior classified by body mass index, postural confidence and balance ability by using statistics Kruskal-Wallis test found that different levels of confidence in balance, there were significant differences in the mean values ​​of fall preventive behaviors with statistical significance .01 (p<.001). Correlation analysis between osteoarthritis severity and fall preventive behavior of osteoarthritis found that osteoarthritis severity had negative correlation with fall prevention behavior at the level .05 statistical significance (rs =-0.14, p<.05).